2011
DOI: 10.5539/jsd.v4n5p196
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment and Mapping of Gully Erosion Hazards in Abia State: A GIS Approach

Abstract: The issue of gully erosion is of major concern in the south-eastern part of Nigeria. This study adopts Geographic Information Systems (GIS) as a tool to identify and study gully erosion hazards in Abia state. 171 gully erosion sites were coordinated using GPS receivers and overlaid on the soil and geological maps of the study area. Spatial database for erosion sites was created using relational database model. Additional 35 gully erosion sites were identified from the processed digital elevation model (DEM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 2 publications
0
20
0
2
Order By: Relevance
“…(Adaptado de De Ploey, 1983;Lourenço et al, 1990;Favis-Morlock, 1996;Samani et al, 2010;Martins 2010;Nwilo et al, 2011). Lourenço et al, 1990;FavisMorlock, 1996;Samani et al, 2010;Martins 2010;Nwilo et al, 2011).…”
Section: Processos Fundamentais Na Génese E Evolução Das Ravinasunclassified
See 1 more Smart Citation
“…(Adaptado de De Ploey, 1983;Lourenço et al, 1990;Favis-Morlock, 1996;Samani et al, 2010;Martins 2010;Nwilo et al, 2011). Lourenço et al, 1990;FavisMorlock, 1996;Samani et al, 2010;Martins 2010;Nwilo et al, 2011).…”
Section: Processos Fundamentais Na Génese E Evolução Das Ravinasunclassified
“…Na maioria das vezes, promovem a concentração da escorrência, como sucede no exemplo em estudo, e a diminuição da infiltração. Alguns estudos têm demonstrado a rápida aceleração na evolução e formação de ravinamentos, associado, por exemplo, à construção de estradas (Reid e Dune, 1996;Nyssen et al, 2002;Douglas e Pietroniro, 2003;Ezezika e Adetona, 2011), pelo que não é de estranhar o aumento no número de trabalhos consagrados ao estudo sobre as ravinas quando associado a problemas de erosão (Bocco, 1991;Martinez-casasnovas et al, 2003;Kheir et al, 2007;Samani et al, 2010;Martins, 2010;Nwilo et al, 2011).…”
Section: Introductionunclassified
“…Gully erosion has attracted the attention of researchers in Nigeria for many years. [23] adopted Geographic Information Systems (GIS) as a tool to identify and study gully erosion hazards in Abia State, southeastern Nigeria. They found that gully erosion sites were well dispersed around false bedded sandstone geological formation.…”
Section: Geohazards In Nigeriamentioning
confidence: 99%
“…It usually starts unnoticed as a result of raindrop impact, washing away by running water which creates rills that later develop into gullies [10]. The status of the southeastern part of Nigeria as a rainforest zone has now been devastated by the action of gullies [11].…”
Section: The Menace Of Gully Erosion In the Eastmentioning
confidence: 99%